PERILAKU LENTUR PADA BALOK BETON SERAT BESI BERLUBANG MENERUS DI DAERAH TARIK - Erlina Prasetyawati; Mochamad Solikin (Politeknik Negeri Semarang, 2021)
Concrete beams that receive a positive bending force, at the top will experience a compressive force while at the bottom receive a tensile force. The theory that reinforced concrete is a structural system where the steel or reinforcement in the concrete functions to withstand tension, then the concrete below the neutral line does not receive a compressive force but transmits a tensile force to the reinforcement. This study analyzes and reduces the area in the tensile area by continuously installing 2 inch diameter PVC pipes and adding fiber to the concrete. This reduction in area is expected to reduce weight and material savings without reducing its strength. This research was carried out with a sample of 28 days old concrete blocks with quality f'c = 21.04 MPa with dimensions of 12 cm x 18 cm x 250 cm, with 4Ø10 mm reinforcement with quality fy = 450 MPa. Concrete beams are made in 3 variations in the form of solid beams, hollow beams without fiber, hollow beams with fiber. Each variation has 2 samples. From the test results, all beams experienced flexural cracks which were characterized by cracks perpendicular to the beam axis and flexural strength behavior which the difference was not significant. From the three variations of this beam, it shows that the results of the hollow beam with the addition of fiber have a greater first crack load. The addition of fiber is able to slow down the cracks that occur and contribute to withstand tensile stresses so that the beam still has strength to bear the load even though cracks have occurred. Based on the calculation simulation, in order to equalize the strength of the hollow beam with fiber, the dimensions of the solid beam need to be enlarged so that the solid beam becomes more expensive. This shows that hollow beams with fiber are more economical than solid beams.